Cognitive Behavioral Counseling Using Cognitive Restructuring Techniques to Enhance Self-Disclosure and Psychological Well-Being - Muhamad Safiul Umam; Kadek Suranata; Luh Putu Sri Lestari (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The background of this study highlights the low levels of self-disclosure and psychological well-being among students, which negatively impact emotional development, social relationships, and academic achievement. This research aims to examine the effectiveness of cognitive-behavioral counseling services using cognitive restructuring techniques in improving students’ self-disclosure and psychological well-being. The study employed a quantitative approach with a quasi-experimental design, involving 60 students selected purposively based on pretest results and divided into experimental and control groups. The instruments used were validated and reliable self-disclosure and psychological well-being questionnaires. Data were analyzed using MANOVA after meeting the assumptions of normality, homogeneity, and multicollinearity. The findings revealed significant improvements in both variables in the experimental group compared to the control group. Cognitive restructuring techniques proved effective in helping students replace negative thinking patterns with more adaptive ones, thereby fostering self-disclosure and enhancing psychological well-being. These findings underscore the importance of integrating cognitive-behavioral techniques into school counseling programs to promote emotionally and socially healthy individuals.